Rage attacks in Tourette Syndrome and Chronic Tic Disorder: a systematic review. (December 2020) - Conte, Giulia; Valente, Francesca; Fioriello, Francesca; Cardona, Francesco
Highlights: Rage attacks (RA) are overlooked and disabling symptoms in tic disorders. Findings support the high prevalence of RA, though estimates range from 20 to 67%. RA and aggressive behaviors appear to be directly related to tic severity. Influence of comorbidities is controversial, with patients with ADHD most at risk. Abstract: Tourette syndrome (TS) and chronic motor/vocal tic disorder (CTD) are neurodevelopmental conditions defined by the occurrence of multiple tics. Besides the well-known association with attention deficit/hyperactivity disorder (ADHD) and obsessive-compulsive disorder (OCD), rage attacks (RA) represent common and detrimental symptoms for patients. Inorder to explore prevalence of RA in tic disorders, relation to tic severity/comorbidities and available treatments, we performed a systematic literature review based on PRISMA Guidelines. 32 studies published between January 2008 – December 2019 were deemed suitable for the analysis and provided a prevalence of 20–67 %. Most findings showed a direct correlation with tic severity and a significant impact on psychosocial functioning. Although apparently related to comorbid ADHD, RA also frequently occur as independent manifestations. Association with other comorbidities, such as OCD, impulse control and mood disorders has also been reported, not yet fully established. Behavioral interventions appear to be effective, whereas there is limited evidence concerning the efficacy of medication. In TS/CTD, RA may be regarded as a major comorbidity that requires clinical investigation in order to develop personalized treatments.